Accounting for Zakat and Infaq (Sadaqah) at Badan Amil Zakat Nasional (BAZNAS) in North Sulawesi, Indonesia - Nur Fitry Latief (AIBPM Publisher, 2019)
This study has purpose to identify the implementation PSAK No. 109 about accounting for Zakat and Infaq (Sadaqah) and describe its procedures and implications byusing qualitative approach. This study was using primary and secondary data. The primary data are derived from field research in the form of data obtained from informants, namely BAZNAS administrators and compulsory zakat (muzaki) and the secondary data consisted of various fiqh literature which contained a discussion about zakat. In addition, secondary data was also extracted from a number of BAZNAS in the form of zakat management accounting report documents. The data collection method were interviews, observation, documentation and literature study. The three sets of data analysis methods are applied as follows data reduction, data display and conclusion drawing. The results indicate that collecting of zakat from mustahik is done by means of socialization to the community and forming a Zakat Collection Unit while the distribution of zakat is done to the muzaki through several programs with allotment categories to 7 of 8 asnaf who are entitled to receive. Data from muzaki and mustahik are collected and included in the application of BAZNAS Information System (SIMBA) and then processed by this application to produce the financial reports.This study has implications for the need and competent human resources in the management of zakat including the field of Accounting and Sharia Management alsoto the need for internal supervision (auditors) and equipping BAZNAS organizations with personnel who are also fully responsible in each field. Keywords: Accounting, Zakat, Infaq, Sadaqah.